Migration in Southern Africa IMISCOE Regional Reader - Rugunanan, Pragna; Xulu-Gama, Nomkhosi (IMISCOE Research Series, 2022)
This open access Regional Reader proposes new ways of theorizing migration in Southern Africa by arguing that traditional western forms of theorizing do not adequately fit the South-South migration context. It explores the existing definitions of a 'migrant' with a view to conceptualise a definition which will speak to the complexities, envisioning a more inclusive Southern African region. The book investigates the various levels of migration moving from the local (rural to urban and urban to rural) to cross border migration; middle-class versus working-class migrant household livelihoods; livelihoods procurement versus wage earning; social capital (networks) and how they make meaning of their circumstances in a 'foreign' space. It also acknowledges the intertwined issues of gender and class as important in analyzing migration processes and the chapters feature both in varying dimensions. As such, the book provides a great resource for students, academics and policy makers.